2006
DOI: 10.1086/504419
|View full text |Cite
|
Sign up to set email alerts
|

A Unified Fitting of Hiand HeiiLyα Transmitted Flux of QSO HE 2347−4342 with ΛCDM Hydrodynamic Simulations

Abstract: Using cosmological hydrodynamic simulations of the ÃCDM model, we present a comparison between the simulation sample and real data sample of H i and He ii Ly transmitted flux in the absorption spectra of the QSO HE 2347À4342. The ÃCDM model is successful in simultaneously explaining the statistical features of both H i and He ii Ly transmitted flux. It includes the following features: (1) The power spectra of the transmitted flux of H i and He ii can be well fitted on all scales !0.28 h À1 Mpc for H and !1.1 h… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

2006
2006
2009
2009

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 32 publications
2
17
0
Order By: Relevance
“…Zheng et al (2004) even find that turbulent broadening is dominant. This finding has been confirmed by Liu et al (2006) who compared the observations to cosmological hydrodynamical simulations. Also Bolton et al (2006) argue that thermal broadening is supposed to be negligible, since Hubble broadening is expected to be the dominant contribution to the width of Lyα forest lines.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…Zheng et al (2004) even find that turbulent broadening is dominant. This finding has been confirmed by Liu et al (2006) who compared the observations to cosmological hydrodynamical simulations. Also Bolton et al (2006) argue that thermal broadening is supposed to be negligible, since Hubble broadening is expected to be the dominant contribution to the width of Lyα forest lines.…”
Section: Discussionsupporting
confidence: 55%
“…Telfer et al 2002) and finite lifetimes, local density variations of the IGM (Miralda-Escudé et al 2000) or filtering of radiation by radiative transfer effects (Maselli & Ferrara 2005). Furthermore, it has been shown that also the noise level of the observed spectra contributes to the scatter in η (Fechner et al 2006a;Liu et al 2006). …”
Section: Introductionmentioning
confidence: 99%
“…Thermal broadening becomes important in collapsed structures at high column densities. In simulations of the Lyα forest, non-thermal broadening has been found to dominate (Zhang et al 1995(Zhang et al , 1998Hernquist et al 1996;Weinberg et al 1997;Bolton et al 2006;Liu et al 2006). This has been confirmed observationally for the low-column density forest (Z04; Rauch et al 2005).…”
Section: Uncertainties In the Spectral Hardnessmentioning
confidence: 99%
“…However, this result is based on a limited statistical sample of 8 absorbers. Liu et al (2006) claimed to confirm this finding using hydrodynamic simulations. On the other hand, Fechner & Reimers (2007) showed that statistically, lines with apparent low η values are often dominated by thermal broadening.…”
Section: Send Offprint Requests To: C Fechnermentioning
confidence: 80%
“…This is due to the fact that any line profile model recovers the observed data only imperfectly. Additionally, the high noise level of the FUSE data introduces further uncertainties (see also Liu et al 2006). Since these problems are inevitable, we expect that our results can be interpreted statistically but conclusions for single absorbers should be considered very carefully.…”
Section: Methodsmentioning
confidence: 91%